Fleabag. Season 2 [videorecording (DVD)] - Waller-Bridge, Phoebe, 1985-; Waller-Bridge, Phoebe, 1985-; Waller-Bridge, Phoebe, 1985-; Colman, Olivia; Gelman, Brett, 1976-; Scott, Andrew, 1976 October 21- (Screen Media, 2020)
It is a hilarious and poignant window into the mind of a dry-witted, sexual, angry, grief-riddled woman, as she hurls herself at modern living in London. This time around, she's coping with her father's upcoming nuptuals, and her attraction to the hot priest they've chosen to officiate, while the brother-in-law escalates everything around him.